2020
DOI: 10.1016/j.nicl.2020.102463
|View full text |Cite
|
Sign up to set email alerts
|

Histological correlates of hippocampal magnetization transfer images in drug-resistant temporal lobe epilepsy patients

Abstract: Highlights Hippocampal MTR in TLE does not add to volume or T2 signal regarding lateralization. Extracellular CSPG are the most relevant correlate to MTR in hippocampal sclerosis. Increased CSPG counterbalances neuron loss over the reduction in hippocampal MTR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…FCDII cases often present daily seizures, in contrast with HS, and have frequent interictal discharges. 8,9 As the frequency of interictal spikes, besides other interictal EEG abnormalities, are directly associated with the density of dysmorphic neurons in the seizure onset zone, 9 the low number of dysmorphic cells in our patient may account for the lower frequency of spikes detected in scalp EEG.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…FCDII cases often present daily seizures, in contrast with HS, and have frequent interictal discharges. 8,9 As the frequency of interictal spikes, besides other interictal EEG abnormalities, are directly associated with the density of dysmorphic neurons in the seizure onset zone, 9 the low number of dysmorphic cells in our patient may account for the lower frequency of spikes detected in scalp EEG.…”
Section: Discussionmentioning
confidence: 68%
“…19 Regardless of the induction mechanism (i.e., mutation of FCDII or inflammation in encephalitis), mTOR pathway dysregulation may be the cause for these dysmorphic neurons in HS, as it is known that chronic inflammation can be seen in HS. 8 However, why only some HS patients present with dysmorphic-like neurons remain unknown.…”
Section: F I G U R Ementioning
confidence: 99%
“…On visual inspection, while in most patients HS is seen as reduced hippocampal volume and increased T2 signal on MRI [24][25][26], FCDs can be seen as cortical thinning (FCD I) or cortical thickening (FCD II), blurred grey -white matter transition, increased T2 signal sometimes as a characteristic transmantle sign, and water diffusion changes [22,[27][28][29][30]. LEATs present a wide range of MRI changes, such as the well-defined "bubbly" appearance of DNETs or the less defined lesion with perilesional T2 hypersignal, contrast enhancement, and calcifications that characterize the gangliogliomas [23,31].…”
Section: Qualitative and Quantitative Mri In Drug-resistant Epilepsymentioning
confidence: 99%
“…However, some hippocampal sclerosis cases have no significant volume loss [46,52]. In these HS cases with normal volume, other tissue changes can influence the hippocampal volume and help hide neuron loss in some cases [46], and measurement of T2 relaxation often reveals the epileptogenic hippocampus [25,53]. A study with MRI-negative FCDs showed that volume-based morphometry identified atrophy in seven cases [54].…”
Section: Qualitative and Quantitative Mri In Drug-resistant Epilepsymentioning
confidence: 99%
See 1 more Smart Citation